2022
DOI: 10.5510/ogp2022si200737
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for the introduction of SWAG at the fields of PJSC «Tatneft»

Abstract: The results of laboratory studies of filtration processes on models of a terrigenous reservoir are presented in order to develop optimal compositions for simultaneous water and gas injection and foam assisted water alternating gas injection on the reservoir. The experiments were carried out on rock samples drilled from the core of terrigenous deposits of the Kynovsko-Pashiy horizon. The use of water-gas mixtures with foam-forming surfactants taking into account the field conditions of the fields of PJSC TATNEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Pump-ejector systems (PES), namely liquid-gas ejector and booster pump are dispersing devices. By grinding gas bubbles and increasing the mixture injection pressure into the formation, PES help to suppress the coalescence of gas bubbles [5]. However, during the injection process, it is impossible to avoid the separation of the mixture into individual components without the addition of agents, the purpose of which is to suppress the adhesion of gas bubbles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pump-ejector systems (PES), namely liquid-gas ejector and booster pump are dispersing devices. By grinding gas bubbles and increasing the mixture injection pressure into the formation, PES help to suppress the coalescence of gas bubbles [5]. However, during the injection process, it is impossible to avoid the separation of the mixture into individual components without the addition of agents, the purpose of which is to suppress the adhesion of gas bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…To regulate the operation of the system with varying gas flow rates, the possibility of frequency regulation of the rotation of the pump shaft is proposed. In [5], experimental studies have shown that for the conditions of a particular field, when preparing a water-gas mixture, it is necessary to choose a surfactant based on the properties of the foams that are obtained by adding each specific surfactant and their ability to displace residual reserves. It was established that the addition of surfactants has a positive effect on the operation of the booster pump.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation